PERDAGANGAN INFORMAL PELINTAS BATAS DI KABUPATEN MALINAU DAN SERAWAK MALAYSIA - Syachrumsyah Asri; Muhammad Nizar Hidayat (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research discloses and describes how cross-border trade and its implications for improving people's welfare in Malinau district of East Kalimantan, especially in border villages. The factors behind the cross-border trade are: topographical and geographical factors, accessibility factors, cost and price factors, and cultural background and emotional relations. The pattern of trade that developed in recent years is no longer in the pattern of direct barter alone but has developed into direct trading patterns. The results show that the results of the development process still tend to be urban bias and less to reach areas that are far from the